Law for computer scientists and other folk - Hildebrandt, Mireille (Oxford : Oxford University Press, 2020)
This is a textbook on law for computer scientists and many others with no wish to become a lawyer, who are nevertheless in need of a proper introduction to how law operates and how it affects individuals, societies and others. It introduces: privacy and data protection, cybercrime, copyright, private law liability and legal personhood.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 16, 2020).
Keywords: Computers -- Law and legislation; Internet -- Law and legislation; Privacy, Right of; Computer crimes; Copyright; Liability (Law); Law; Laws of specific jurisdictions & specific areas of law